2017
DOI: 10.7717/peerj.3662
|View full text |Cite
|
Sign up to set email alerts
|

The key role of microtubules in hypoxia preconditioning-induced nuclear translocation of HIF-1α in rat cardiomyocytes

Abstract: BackgroundHypoxia-inducible factor (HIF)-1 is involved in the regulation of hypoxic preconditioning in cardiomyocytes. Under hypoxic conditions, HIF-1α accumulates and is translocated to the nucleus, where it forms an active complex with HIF-1β and activates transcription of approximately 60 kinds of hypoxia-adaptive genes. Microtubules are hollow tubular structures in the cell that maintain cellular morphology and that transport substances. This study attempted to clarify the role of microtubule structure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Conversely, other studies have reported that hypoxia reduces microtubule stability and polymerization (95, 96). Despite these conflicting results, other studies have shown that stabilizing microtubules during hypoxia is critical for the nuclear translocation of HIF1 α and for enhancing the chemoresistance of tumor cells (9799). Chronic hypoxia suppresses the nuclear translocation of HIF1 α by disrupting the microtubule network, which can be recovered by taxol (a microtubule stabilizer) pretreatment (97).…”
Section: Hif1α Regulatory Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies have reported that hypoxia reduces microtubule stability and polymerization (95, 96). Despite these conflicting results, other studies have shown that stabilizing microtubules during hypoxia is critical for the nuclear translocation of HIF1 α and for enhancing the chemoresistance of tumor cells (9799). Chronic hypoxia suppresses the nuclear translocation of HIF1 α by disrupting the microtubule network, which can be recovered by taxol (a microtubule stabilizer) pretreatment (97).…”
Section: Hif1α Regulatory Factorsmentioning
confidence: 99%
“…Despite these conflicting results, other studies have shown that stabilizing microtubules during hypoxia is critical for the nuclear translocation of HIF1 α and for enhancing the chemoresistance of tumor cells (9799). Chronic hypoxia suppresses the nuclear translocation of HIF1 α by disrupting the microtubule network, which can be recovered by taxol (a microtubule stabilizer) pretreatment (97). In addition, stabilized microtubule inhibits Ran-mediated VHL nuclear translocation, leading to the stabilization of HIF1 α in the nucleus (100).…”
Section: Hif1α Regulatory Factorsmentioning
confidence: 99%
“…HIF1 is activated through strict control of its alpha subunit (HIF1α) by transcription, translation, posttranslational modification like prolyl-or asparaginyl hydroxylation and ubiquitination, and microtubule-associated nuclear transportation. However, the HIF1 beta subunit (HIF1β) is constitutively expressed and does not possess an oxygen-dependent degradation domain [31][32][33][34] . Therefore, it has been suggested that HIF1α plays an important role in the HIF1-regulated metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Protective GPCR signaling involves interaction with G proteins to communicate extracellular messages to intracellular effectors such as phospholipase C, AC, and ion channels (Eschenhagen, 1993;Novotny and Svoboda, 1998;Novotny et al, 1999Novotny et al, , 2001. In addition, activated Ga s acts as an intracellular messenger to modulate microtubule dynamics (Yu et al, 2009), key to cell morphology and intracellular signaling, and is implicated in preconditioning (Guo et al, 2017). Curiously, prior work implicated both stimulatory Ga s and inhibitory G i proteins in SLP protection (Peart and Gross, 2006), whereas acute morphine protection appears to be G i mediated.…”
Section: Discussionmentioning
confidence: 99%